"We want what's best for patients." nurse leaders' attitudes about medical cannabis: A qualitative study - Ellen T. Kurtzman; Jessica Greene; Robyn Begley; Karen Neil Drenkard (Elsevier, 2022)
Background: The majority of states have legalized medical cannabis. Nurse leaders must be prepared for an increase in patients' use of the drug across all care settings. Objectives: To explore nurse leaders' attitudes towards, knowledge of, and experiences with medical cannabis. Design: : Descriptive qualitative study design. Participants: 28 nurse leaders-19 in four focus groups of 3-7 participants and another 9 in interviews. Methods: Semi-structured, one-on-one interviews and focus groups of nurse leaders about their attitudes towards and experiences with patients' use of medical cannabis. Thematic analysis was used to identify themes and subthemes. Results: Four major themes were identified: overwhelming support for legalized medical cannabis; importance of overcoming the stereotype of a gateway drug; problematic mismatch between federal and state cannabis policies; and nursing needs to be move involved. Conclusions: There was strong support for legalized medical cannabis to meet patients' needs; yet, respondents reported little discussion about or education regarding medical cannabis among nurses. Inconsistent federal and state cannabis policies were viewed as especially problematic and in need of alignment.